Bilateral internal thoracic artery grafting in children under 5 years of age with Kawasaki disease: a case series. Issue 6 (22nd November 2020) - Shimahara, Yusuke; Fukushima, Satsuki; Tadokoro, Naoki; Tsuda, Etsuko; Hoashi, Takaya; Kitamura, Soichiro; Kobayashi, Junjiro; Fujita, Tomoyuki
Abstract: Background: Although persistent coronary artery aneurysm of Kawasaki disease (KD) is rare, some patients develop a life-threatening myocardial infarction. In paediatric coronary artery bypass surgery (PCABS), the internal thoracic artery (ITA) graft is a reliable graft with favourable coronary outcomes. However, few studies have reported the outcomes and technical considerations of PCABS using bilateral ITAs in small children who have multivessel disease. Case summary: We present the cases of three children under 5 years of age who underwent PCABS utilizing bilateral ITAs. All three patients had known bilateral giant coronary aneurysms associated with KD. Paediatric coronary artery bypass surgery was indicated after confirming multiple coronary lesions with myocardial ischaemia. One child underwent emergency PCABS because of circulatory collapse. The arterial anastomoses were performed under cardioplegic arrest. The left ITA was anastomosed to the left anterior descending artery (LAD) or the circumflex artery. The right ITA was anastomosed to the right coronary artery or the LAD. Post-operative coronary angiography revealed patent bilateral ITA grafts with an excellent run-off in all patients, and none of them have suffered any subsequent coronary event. Discussion: Bilateral ITA grafting is a feasible procedure with favourable coronary outcomes for treating small children with multivessel disease, even in the setting of circulatory collapse.